Corporate Governance Overview- The Saudi Arabian Context - Kartinah, Binti Ayupp; Norizan, Binti Jaafar; Lubna, Javed Rizvi (The Mattingley Publishing Co., Inc., 2019)
Corporate governance refers to internal arrangement that encompasses procedures, practices and individuals, which aids the needs of stockholders and other investors, by guiding and monitoring organization actions with good corporate savvy, fairness and honesty. Good Corporate governance supports impartiality, honesty, and transparency in its accountabilities to investors. Good corporate governance practices simplifies economic competence by concentrating on value-enhancing actions and aids proficient distribution of scarce resources. This is accomplished when corporations proficiently employ their resources, attract low cost capital, meet societal anticipations and improve overall performance. This paper discusses different frameworks with their critical analysis. Moreover this paper sheds the light on Saudi Arabian Corporate governance arrangements and their legal context.